Effects of web design quality and media publicity on job applicants. - Lin, Shihui. (2008)
The aim of this study was to investigate the effects of media publicity and company’s website on organizational attractiveness and job application tendency. A 3 x 2 factorial design was formulated to test our hypotheses. We proposed that as web design quality increases, perceived organizational attractiveness and job application tendency would increase. Similarly, as media publicity gets more positive, perceived organizational attractiveness and job application tendency will increase. We made a prediction that influence of media publicity on perceived organizational attractiveness could be moderated by web design quality. We also suggested the influence of web design quality on job application tendency of applicants could be moderated by media publicity. Results from 180 business undergraduates confirmed all the hypotheses except the hypothesis that web design quality influenced job application. Research implications and future research were also discussed.